Prompt searches for optical signals from gravitational wavetransient candidates with Pi of the Sky - Zadrozny, A.; Sokolowski, Marcin; Opiela, R.; Obara, L. (SPIE, 2013)
The aim of the paper is to show methods used by Pi of the Sky team to search for optical counterparts of GW event candidates during Looc-Up science run and methods that we are planning to develop as part of the future Looc-Up. During the future joint GW-EM observations a new Pi of the Sky telescope unit could image more than 1/3 of GW candidate probability maps in less than 10 minutes, taking many pictures of the same observation field. The system could automatically recognize optical transients and perform follow-ups of interesting events.